GLOBAL HALAL INDUSTRY: REALITIES AND OPPORTUNITIES - Azam, Md Siddique E; ABDULLAH, MOHA ASRI (UNISSULA, 2020)
The purpose of this study is to realize the opportunities of Halal industry exploring the driving factors of this fastest growing industry in the world. The global Halal industry as a whole is estimated to worth around USD2.3 trillion (excluding Islamic finance) a year, is now one of the fastest growing markets. Simultaneously, the global market growth is estimated to reach at an annual rate of 20 percent per annum. Such expansion of the industry is because the global halal market of 2.18 billion Muslims is no longer confined Muslims only. Similarly, the Halal industry is no longer confined to food and food-related products, but rather to include pharmaceuticals, cosmetics, health products, toiletries and medical devices as well as service sector components such as logistics, marketing, print and electronic media, packaging, branding, and financing. This paper attempts to examine the current realities of the global halal industry by observing the factors determining such increasing demand for Halal industry in addition to the opportunities that are offered from on recent global development in the market. According to the Islamic rules and regulations the word halal is rooted from an Arabic word which means ‘permissible’ or ‘lawful’. The concept of halal is not bound to food-related items only but to multiple other aspects such as products, which can be further categorized into various groups, for instance, cosmetics, self-care, health, tourism and services. A global survey discovered that the Muslims spend on food, beverages and lifestyles amounting to USD2 trillion in 2016. Moreover, the global Muslim market spends on travel reaching USD169 billion in 2016 and expected to increase to USD283 billion in 2022. Meanwhile, the Muslim average per capita income (GDP) has risen from USD1763 to USD6530 from 1993 to 2010. To achieve the objectives of the study, a methodology of analyzing secondary data was adopted in this paper. The sources of all secondary data and information were extensive literature review, library search, a number of different websites, online journal publications, conference proceedings, thesis, different institutional reports and publications. The findings show that there are three major factors driving the rapidly growing global halal market. First, sizable and growing Muslim population at 1.8 per cent per annum, Second, growing economic development and hence increasing purchasing power among the Muslim. Lastly, emergence of the potential halal market in non-Muslim nations and halal industry players. Nonetheless, numerous challenges confronting Halal industry players. These include the standardization of halal, lack of data, animal right, halal is not compulsory in many Muslim countries and others. As a way forward, industry players need to deepen knowledge and understanding of the Muslim market (pattern and behavior), regularly update data, and exploit untapped market niches as well as product sales and promotion. Findings and recommendations of this work will be a great resource for future researchers and scholars in relevant areas as well as policy makers to make their strategic decisions in the fields of Halal Industry.